“When You Make a Movie, and You See Your Story There, You Can Hold It”: Qualitative Exploration of Collaborative Filmmaking as a Therapeutic Tool for Veterans - Tuval-Mashiach, Rivka; Patton, Benjamin W.; Drebing, Charles (Frontiers in Psychology, 2018)
Despite the availability of effective treatments for coping with traumatic experiences, a large percentage of military veterans in need do not seek help. The "I Was There" model is a new filmmaking program which is a creative-expressive tool, developed to enable veterans to reflect on their experiences and jointly create short artistic films. These artistic films articulate, often metaphorically, aspects of the veterans’ service experiences, traumatic events, and reintegration challenges. The current study employed a qualitative methodology to explore participants’ subjective experience of the program. We interviewed 50 participants following the intervention, focusing specifically on their perceptions of the filmmaking process, the aspects they viewed as meaningful, and whether and how the process affected them. Most participants reported their experience as positive and empowering. Three overarching themes emerged as significant in describing the benefits of participation: Gaining a new sense of agency, regaining a sense of affiliation, and processing the trauma. The findings are illustrated and discussed within the context of narrative therapy, as is the potential of video-based therapy, especially regarding non-articulated, sensory traumatic memories, and for the process of (re)construction of the trauma narrative.